Prognostic association of frailty with post-arrest outcomes following cardiac arrest: A systematic review and meta-analysis. (October 2021) - Mowbray, Fabrice I.; Manlongat, Donna; Correia, Rebecca H.; Strum, Ryan P.; Fernando, Shannon M.; McIsaac, Daniel; de Wit, Kerstin; Worster, Andrew; Costa, Andrew P.; Griffith, Lauren E.; Douma, Matthew; Nolan, Jerry P.; et al.
Highlights: Frailty is a robust predictor of patient-important health outcomes and is often overlooked. Individuals with frailty have approximately 3× the odds of dying during hospitalization after in-hospital cardiac arrest. Frailty should be considered during shared-decision making about end-of-life care. Abstract: Objective: To synthesize the current evidence examining the association between frailty and a series of post-arrest outcomes following the provision of cardiopulmonary resuscitation (CPR). Data sources: We searched MEDLINE, PubMed (exclusive of MEDLINE), EMBASE, CINAHL, and Web of Science from inception to August 2020 for observational studies that examined an association between frailty and post-arrest health outcomes, including in-hospital and post-discharge mortality. We conducted citation tracking for all eligible studies. Study selection: Our search yielded 20, 480 citations after removing duplicate records. We screened titles, abstracts and full-texts independently and in duplicate. Data extraction: The prognosis research strategy group (PROGRESS) and the critical appraisal and data extraction for systematic review of prediction modelling studies (CHARMS) guidelines were followed. Study and outcome-specific risk of bias were assessed using the Quality in Prognosis Studies (QUIPS) instrument. We rated the certainty of evidence using the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) recommendations for prognostic factor research. Data synthesis: Four studies were included in this review and three were eligible for statistical pooling. Our sample comprised 1, 134 persons who experienced in-hospital cardiac arrest (IHCA). The mean age of the sample was 71 years. The study results were pooled according to the specific frailty instrument. Three studies used the Clinical Frailty Scale (CFS) and adjusted age (our minimum confounder); the presence of frailty was associated with an approximate three-fold increase in the odds of dying in-hospital after IHCA (aOR = 2.93; 95% CI = 2.43–3.53, high certainty). Frailty was also associated with decreased incidence of ROSC (return of spontaneous circulation) and discharge home following IHCA. One study with high risk of bias used the Hospital Frailty Risk Score and reported a 43% decrease in the odds of discharge home for patients with frailty following IHCA. Conclusion: High certainty evidence was found for an association between frailty and in-hospital mortality following IHCA. Frailty is a robust prognostic factor that contributes valuable information and can inform shared-decision making and policies surrounding advance care directives. Registration: PROSPERO Registration # CRD42020212922